Synthesis and Antiviral Activity of Bis-Histidyl Diaminoalkanes in Relation to Feline calicivirus - L. S. Koroleva; L. A. Yarinich; O. V. Semenova; A. G. Glotov; T. I. Glotova; V. N. Silnikov (Антибиотики и Химиотерапия, 2020)
An RNA-containing virus of the Vesivirus genus Caliciviridae family causes feline calicivirosis, a disease widely spread worldwide. The literature describes a systemic form of infection leading to the death of up to 60% of sick animals (FCV-VSD). It is very important to find new chemicals that can effectively inhibit the process of reproduction of the virus due to the lack of means of etiotropic therapy for calicivirus infection in cats (as well as other mammals and humans). It is proposed to use artificial ribonuclease (mRNAse) - low molecular weight compounds capable of efficiently cleaving genomic RNA as antiviral drugs. Three new N,N'-bis-L-histidyl-diaminoalkanes were synthesized in the course of the work, the toxicity and antiviral activity of compounds against RNA-containing Feline Calicivirus (FCV) were studied. The greatest antiviral effect against FCV was shown by N,N'-bis-Na-L-histtdyl-1,10-diaminodecane.